Orientalism on the margins: inter-subjective space in Edward Granville Browne’s A Year amongst the Persians - Pinak, Mohamad Zandy Ali; Lalbakhsh, Pedram (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of the present study is to analyse the image of Iran, created by E. G. Browne (1862-1926) in his travelogue A Year amongst the Persians. In his representation, Browne vacillates between two poles of Romantic and scientific discourses. On the one hand, he is a Romantic wanderer, who embarks on a quest of Departure, Initiation and Return in the space of the Other (Campbell, 2004, p. 28). Based on such an idealistic perspective, in his one year quest in Iran which is mainly spend among the marginalized believers of the Bahai faith, Browne (1893) seeks for a rebirth of the decaying Iranian nation, “which slumbers, but is not dead”(p. 219). On the other hand, Browne (1893) regards himself as an “inquirer” who in his observations maintains a detached scientific perspective towards Iranian culture and society, and does not hesitate to question the principles which he finds unacceptable (p. 529). In the course of his journey, the tension between these two discourses leads to a subversion of both of them, which finally mirrors in a breakdown of Browne’s conception of Self and the Other. Browne’s recognition of the Self and the Iranian nation, at the end of his journey is through the space of inter-subjectivity. This final state of in-betweenness makes it possible for him to recognize the Other from the perspective of cultural difference, through which a possibility is created in his image of Iran to escape the “urge to possess” that the Orientalist discourse of travel writing entails. (Ashcroft, 2009, p. 230)